Improving Students’ Vocabulary Mastery by Using Extensive Reading of Junior High School Students - Evi Sulvia Ningsih; Sujarwo Sujarwo; Hasnani Hasnani; Muliaty Ibrahim (CV. Eureka Murakabi Abadi, 2025)
The purpose of this study was to determine the use of extensive reading methods in teaching vocabulary in the eighth grade at Upt. SMPN Benteng Utara No. 4, Selayar Islands, which consisted of 29 students. This research was action research; it was mentioned that the steps of the research include reconnaissance, planning, action, observation, and reflection to improve students’ vocabulary mastery at VIII A through extensive reading activities. The researcher focused on employing the extensive reading activities to improve students' vocabulary mastery. The aim was to find out or fine the use of extensive reading methods in increasing students' vocabulary to get a significant improvement by comparing the pre-test and post-test in the eighth-grade students based on the analysis of the mean score in the eighth-grade post-test to find out how the use of extensive reading methods affects students' vocabulary. The research showed that the average score in the first cycle is 65,5 and the second cycle is 80,5. It can be concluded that the extensive reading methods are effective in increasing students' vocabulary. This study concludes that extensive reading activities could improve students’ vocabulary mastery. Through this activity, they were familiar with the words they had learnt. They could memorize the words easily because the words were met several times in an extensive reading activity, and they had more opportunities to explore various English texts.